Words of destiny : practicing astrology in North India - Guenzi, Caterina (State University of New York Press, 2021)
Investigates the professional practices of astrologers in urban India and their popularity among the educated middle and upper classes.
Keywords: Hindu astrology -- Social aspects -- India -- Vārānasi (Uttar Pradesh); Predictive astrology.; Astrologers -- India -- Vārānasi (Uttar Pradesh); Astrologie hindoue -- Aspect social -- Inde -- Vārānasi (Uttar Pradesh); Astrologie prédictive.; Astrologues -- Inde -- Vārānasi (Uttar Pradesh); SOCIAL SCIENCE / Anthropology / Cultural & Social.; Astrologers; Hindu astrology -- Social aspects; Predictive astrology; India -- Vārānasi (Uttar Pradesh)